PENGARUH PENGGUNA ANTARMUKA DAN KEAMANAN SITUS TERHADAP KEPUASAN, KEPERCAYAAN DAN LOYALITAS PELANGGAN PADA SITUS BELANJA ONLINE DI INDONESIA - Lule, Benny; Liani, Mitha (JBE (Journal of Business and Economics), 2014)
The purpose of this study is to evaluate the effect of the user interface and security of the website to the satisfaction, trust and customer loyalty. There are 6 hypotheses in this study. In this study, the data obtained through questionnaires distributed online, and also directly with a total sample of 100 respondents. This study used a simple linear regression model to examine the effect of the user interface and security of the website to the satisfaction and trust of customers as well as to test the effect of customer satisfaction and trust on customer loyalty partially. The test results indicate that the user interface and security websites positive effect on customer satisfaction and confidence, as well as customer satisfaction and confidence positive effect on customer loyalty.